Bilateral ischemia of the insular cortex after high altitude climbing: A case report. (September 2019) - D'Arrigo, Andrea Maria; Altavilla, Riccardo; Bartesaghi, Francesca; Floro, Stefano; Campiglio, Laura; Secchi, Manuela; Priori, Alberto
Highlights: High altitude exposure could be related to cerebrovascular events. The exact pathogenic mechanism is not well understood even if several hypothesis have been supposed. Embolic etiology has been proposed by some authors. Right insular cortex may be related to arrhythmias responsible for secondary embolic dissemination. Abstract: High altitude exposure could be related to neurological events such as stroke-like episodes, even if the exact pathogenic mechanism is still debated. We describe the case of a caucasian woman who had a bilateral insular ischemic stroke after a rapid ascent above 4000 m in which a secondary embolic dissemination due to a right insular stroke, maybe related to high altitude hemoconcentration, could be hypothesized. In our opinion a prolonged cardiac rhythm monitoring have to be considered especially when no other embolic sources are found and for lesions involving the insular cortex.